Ovarian Vein Thrombosis: Incidence of Recurrent Venous Thromboembolism and Survival. Issue 5 (November 2017) - Lenz, Charles J.; Wysokinski, Waldemar E.; Henkin, Stanislav; Cohoon, Kevin P.; Casanegra, Ana; Simmons, Benjamin S.; Saadiq, Rayya A.; Daniels, Paul R.; Wysokinska, Ewa M.; Bjarnason, Haraldur; McBane, Robert D.
Abstract : OBJECTIVE: To identify the risk of venous thromboembolism recurrence, major bleeding, and mortality in patients with ovarian vein thrombosis so as to better define optimal treatment strategies. METHODS: Patients with ovarian vein thrombosis (1990–2015) and age- and gender-matched patients with contemporary leg deep vein thrombosis (DVT) were assessed for differences in etiology, venous thromboembolism recurrence, and survival in a case–control study. RESULTS: Over the timeframe of this study, only 219 ovarian vein thrombosis cases were identified compared with 13, 417 leg DVTs. Median duration of follow-up was 1.23 years (interquartile range 0.25–4.14). Pulmonary embolism was identified at presentation in 6% of patients with ovarian vein thrombosis and 16% of those with DVT ( P =.001). Frequent causes of ovarian vein thrombosis included cancer, hormonal stimulation, surgery, and hospitalization. Cancer was twofold more frequent in patients with ovarian vein thrombosis (44% compared with 21%; P <.01). Despite being less frequently treated with anticoagulation (ovarian vein thrombosis 54% compared with DVT 98%, P <.001), venous thromboembolism recurrence rates were similar between groups (ovarian vein thrombosis 2.3 compared with DVT 1.8 per 100 patient-years, P =.49). A personal history of venous thromboembolism and preceding surgery was found to be an independent risk factor for venous thromboembolism recurrence among those treated with anticoagulation (hazard ratio 6.7, P =.04 and hazard ratio 13.6, P =.03, respectively). There was no significant difference in overall survival. CONCLUSION: Ovarian vein thrombosis is a rare thrombotic condition with an incidence 60-fold lower compared with leg DVT in our institution. The striking association with cancer adversely affects overall survival rates in patients with ovarian vein thrombosis. Venous thromboembolism recurrence rates argue for anticoagulation with a direct oral anticoagulant or vitamin K antagonist, particularly in those with a history of venous thromboembolism. Abstract : Ovarian vein thrombosis is a rare thrombotic condition with a striking association with cancer and venous thromboembolism recurrence rates that argue for anticoagulation therapy.